2014
DOI: 10.1038/srep07074
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dynamic structural and mechanical changes of neuroblastoma cells associated with glutamate-mediated neurodegeneration

Abstract: Glutamate-mediated neurodegeneration resulting from excessive activation of glutamate receptors is recognized as one of the major causes of various neurological disorders such as Alzheimer's and Huntington's diseases. However, the underlying mechanisms in the neurodegenerative process remain unidentified. Here, we investigate the real-time dynamic structural and mechanical changes associated with the neurodegeneration induced by the activation of N-methyl-D-aspartate (NMDA) receptors (a subtype of glutamate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 62 publications
(82 reference statements)
0
58
0
Order By: Relevance
“…Acta Pharmacologica Sinica npg stimulation of drugs [51][52][53] to assess the drug actions from the viewpoint of cell mechanics.…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…Acta Pharmacologica Sinica npg stimulation of drugs [51][52][53] to assess the drug actions from the viewpoint of cell mechanics.…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%
“…Studies in the past decade have demonstrated that cell mechanics play an important role in maintaining cellular physiological activities [53,63] . Cells sense external mechanical stimuli and convert them into intracellular chemical signals via proteins on the cell surface to regulate cellular physiological activities [64] .…”
Section: Dynamic Changes Of Cellular Ultra-microstructure and Elasticmentioning
confidence: 99%
See 3 more Smart Citations